Study of the effect of extracts and oils of the local medicinal plant (thyme) in preserving some fish (Comprehensive Journal of Science, 2025)
There is a growing interest in natural ingredients that can be used as preservatives in the foodindustry and preservation. Among the natural materials that can be used for preservation are plantextracts that are extracted from some natural plants, such as thyme (Thymus vulgaris ), The currentwork aimed to study the efficiency of extracts and oils of local medicinal plant (thyme) in preservingfish. Two species of fresh, economical fish writhe(sparus aurata) sardines,( sardine pilchardus )that are widely consumed were collected during May, 2023, each species divided into two grouptype, one of the two were treated with the extracts of these plants and the other group were treatedwith the oils of studied plants demonstrated the effectiveness of these herbs in preserving thesefish. A comparison was made between the effectiveness of extracts and oils from these plants inpreserving the fish studied. The results showed that there were differences between the samplesbefore and after treatment. The results showed that there were differences between the types ofsolutions, indicating that the alcoholic extract is better than the aqueous and oil extracts in theprocess of preserving genetic fish and sardines. There are no differences between the types of plantused in the experiment, which are (thyme,) Whereas a concentration of 20% is better in thepreservation process than a concentration of 10%.